Precipitation, High Temperature and Global Warming as Correlates of Students’ Academic Performance in Public Secondary Schools in Igbokoda Local Government Area of Ondo State. - Ojeniyi, Bolajoko F.; Akinsuroju, Oluwatosin E. (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
This study was carried out to determine how climatic or aerial factors exert influence on students’ academic performance in Public Secondary Schools in Igbokoda Local Government Area of Ondo State. A descriptive survey research design was adopted for the study. Simple random sampling technique was used to select twelve 12 (67%) public secondary schools out of the 18(100%) public secondary schools in the Local Government Area. Stratified proportional random sampling technique was used to select 567 (34.2%) SSS 2 students from the population of 1,640 which make up of the 12 selected public secondary schools. The data collections for the study were two instruments; Precipitation, High Temperature and Global warming Questionnaire (PHTGQ) and Students’ Academic Performance Questionnaire ( SAPQ) that gave r’= 0.81 and 0.75 respectively. Five null hypotheses formulated were tested at 0.05 level of significance. Finding however indicated that Precipitation, High Temperature and Global Warming have significance relationship with students’ academic performance (r = 0.838, P<0.05), (r = 0.475, P< 0.05) and ( r = 0.452, P < 0.05 ) respectively. Findings also revealed that each of the independent variables covered in this study have individual effect on students’ academic performance (R 2 = 0.18, P<0.05).  Findings finally shown that there is a joint or composite significant effect of independent variables on students’ academic performance (F = 483.03, P< 0.05). Based on the above findings, some of the recommendations made include; there should be adequate sensitization and mobilization of both the students and stakeholders in education on the common ways of controlling erosion thudding. Children should be immunized against preventable diseases that come with climate change and should not be allowed or be exposed to heat. Curriculum developer should include environmental education in the curriculum of all levels of education system. Keywords: Precipitation, High Temperature, Global Warming, Academic Performance.